PARTISIPASI MASYARAKAT DALAM PROGRAM PERENCANAAN PEMBANGUNAN KALURAHAN PETIR (Studi Kasus Padukuhan Ngurak-Urak, Kalurahan Petir, Kapanewon Rongkop, Kabupaten Gunungkidul): Studi Kasus Padukuhan Ngurak-Urak, Kalurahan Petir, Kapanewon Rongkop, Kabupaten Gunungkidul - Heri Roh Pujiati; febriana, alma; Ricardho Dhaniel Nugroho (Mimbar Administrasi Mandiri, 2025)
Community participation is an important element in sustainable, transparent and fair village development planning. This research aims to describe the form of participation of the Padukuhan Ngurak-Urak community in planning the development of Petir District, analyze the factors that influence it, and identify obstacles and opportunities to increase participation. This research uses a qualitative descriptive approach with data collection techniques through non-participatory observation and semi-structured interviews with village officials, community leaders and residents. The research results show that community participation occurs in various forms, both formally through the Hamlet Deliberation and Village Head Deliberation, as well as informally through direct communication with village officials. However, participation is still consultative and has not yet reached partnership level. Inhibiting factors include labor migration, limited access to information, and minimal youth involvement in official forums. However, there are positive indications in the form of involvement in community service work, Karang Taruna initiatives, as well as the use of information technology by the sub-district government. In conclusion, community participation in Padukuhan Ngurak-Urak shows a positive trend, but is not yet substantially optimal. Institutional strategies are needed that support increasing community capacity, providing space for inclusive dialogue, as well as funding mechanisms that are responsive to the needs of vulnerable groups and youth.